2022
DOI: 10.1021/acsomega.2c00935
|View full text |Cite
|
Sign up to set email alerts
|

Tritopic Bis-Urea Receptors for Anion and Ion-Pair Recognition

Abstract: This work reports on the synthesis and characterization of three tritopic receptors and their binding properties toward various anions, as their tetrabutylammonium salts, and three alkali metal–acetate salts by UV–vis, fluorescence, 1 H, 7 Li, 23 Na, and 39 K NMR in MeCN/dimethyl sulfoxide (DMSO) 9:1 (v/v). Molecular recognition studies showed that the receptors have good affinity for oxyanions. Furthermore, these compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The Δ E b cp for Cl − in EUPR @Na‐Cl‐Ag and EUPR @Na‐Ag‐Cl are also larger than −151 kcal/mol. It is clear that the enhancement effect of two cation (Na + and Ag + ) is strong than one cation (Na + or Ag + ) introduced into, presenting the features of ion‐pair recognition 45–50 . Especially, the Δ E b cp for Cl − in EUPR @NaAgCl is the largest, manifesting an excellent synergistic regulation performance for chloride anion recognition with two different cationic effectors.…”
Section: Results Adn Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Δ E b cp for Cl − in EUPR @Na‐Cl‐Ag and EUPR @Na‐Ag‐Cl are also larger than −151 kcal/mol. It is clear that the enhancement effect of two cation (Na + and Ag + ) is strong than one cation (Na + or Ag + ) introduced into, presenting the features of ion‐pair recognition 45–50 . Especially, the Δ E b cp for Cl − in EUPR @NaAgCl is the largest, manifesting an excellent synergistic regulation performance for chloride anion recognition with two different cationic effectors.…”
Section: Results Adn Discussionmentioning
confidence: 98%
“…It is clear that the enhancement effect of two cation (Na + and Ag + ) is strong than one cation (Na + or Ag + ) introduced into, presenting the features of ion-pair recognition. [45][46][47][48][49][50] Especially, the ΔE b cp for Cl À in EUPR@NaAgCl is the largest, manifesting an excellent synergistic regulation performance for chloride anion recognition with two different cationic effectors. Na + binding, in turn, can be enhanced by chloride anion, whereas it seems that Ag + binding cannot always be enhanced by chloride anion.…”
Section: Binding Energy Analysismentioning
confidence: 99%
“…There are limited reports in the literature on the strong affinity of anions to the NH groups of the urea and urethane functionality 53 . Regarding the mechanism of this phenomenon, it was suggested that in short distances, weaker forces like hydrogen bonding could overcome the strong ionic interactions leading to aggregation of anions stabilized by its environment 54,55 . It is evident that the urea‐urethane functionalities were quite successful at immobilizing the anions while the oxygen atoms in PEO and PCL were responsible for coordination with Li+$$ {\mathrm{Li}}^{+} $$.…”
Section: Resultsmentioning
confidence: 99%
“…53 Regarding the mechanism of this phenomenon, it was suggested that in short distances, weaker forces like hydrogen bonding could overcome the strong ionic interactions leading to aggregation of anions stabilized by its environment. 54,55 It is evident that the urea-urethane functionalities were quite successful at immobilizing the anions while the oxygen atoms in PEO and PCL were responsible for coordination with Li þ . In a recent report, it was shown that ionomers of WPU were able to limit the mobility of counter anions and the high t Liþ was attributed to the ionomers present in the WPU structure.…”
Section: Electrochemical Activitymentioning
confidence: 99%
“…24 Gomez-Vega, Lara, and co-workers have also reported bisurea linked through a polyether bridge for ion-pair recognition. 25 In addition, flexible butyl, sterically bulky tert -butyl, and aromatic phenyl groups have been introduced as terminal groups to compare the solubilities and the binding abilities of the receptors.…”
Section: Introductionmentioning
confidence: 99%